Sentencing Disparities for Violence against Children Resulting in Death: A Study of Sibuhuan District Court Decision Number 103/Pid.Sus/2020/PN Sbh - Butar-Butar, Kornelius; Risdalina, Risdalina; Kusno, Kusno (SIGn Jurnal Hukum, 2025)
Criminal law enforcement in cases of collective violence frequently encounters challenges in determining the proportionality of punishment. This challenge arises primarily when Public Prosecutors submit uniform sentencing demands for all defendants without dissecting their respective gradations of culpability. This research aims to analyze the urgency of applying the principle of individualized punishment to correct uniform demands in participation (deelneming) cases. Furthermore, this study evaluates the judicial ratio decidendi in imposing sentencing disparities to achieve substantive justice. This study is a normative-juridical legal research employing a case approach toward Decision Number 103/Pid.Sus/2020/PN Sbh. The results indicate a significant asymmetry in factual roles among the defendants. The initiator of the violence possessed a more dominant causal contribution toward the death of the child victim compared to other participating perpetrators. The Judges performed a judicial correction by handing down a verdict exceeding the demand (ultra petita) in favor of the initiator and a conforming verdict in favor of the follower. This sentencing disparity is not assessed as a form of inconsistency; rather, it constitutes a manifestation of proportional justice oriented toward child victim protection (victim-oriented justice). This research concludes that, in participation offenses resulting in fatalities, justice does not lie in equal sentencing, but in the precision of imposing sanctions commensurate with the gravity of the perpetrator’s role and fault.